Genetic characterization of a unique neuroendocrine transdifferentiation prostate circulating tumor cell-derived eXplant model - Vincent Faugeroux; Emma Pailler; Marianne Oulhen; Olivier Déas; Laura Brullé-Soumaré; Céline Hervieu; Virginie Marty; Kamélia Alexandrova; Kiki Andree; Nikolas H. Stoecklein; Dominique Tramalloni; Stefano Cairo; et al. (2020)
Transformation of castration-resistant prostate cancer (CRPC) into an aggressive neuroendocrine disease (CRPC-NE) represents a major clinical challenge and experimental models are lacking. A CTC-derived eXplant (CDX) and a CDX-derived cell line are established using circulating tumor cells (CTCs) obtained by diagnostic leukapheresis from a CRPC patient resistant to enzalutamide. The CDX and the derived-cell line conserve 16% of primary tumor (PT) and 56% of CTC mutations, as well as 83% of PT copy-number aberrations including clonal TMPRSS2-ERG fusion and NKX3.1 loss. Both harbor an androgen receptor-null neuroendocrine phenotype, TP53, PTEN and RB1 loss. While PTEN and RB1 loss are acquired in CTCs, evolutionary analysis suggest that a PT subclone harboring TP53 loss is the driver of the metastatic event leading to the CDX. This CDX model provides insights on the sequential acquisition of key drivers of neuroendocrine transdifferentiation and offers a unique tool for effective drug screening in CRPC-NE management.